Study the Antibacterial Activity of Bacteriocin Produced from the Locally Isolated Cronobacter sakazakii - Jasim, Hameed M; Zbar, Nedhaal S; Al-Roubaiee, Mahaba R (Al-Nahrain Journal of Science, 2018)
Cronobacter sakazakii was isolated from food samples and identified using morphological, biochemical tests and VITEK-2 system to produce bacteriocin by induction with mitomycin-C. C.sakazakii isolates were screened for their ability for bacteriocin production. Result showed that all these isolates were bacteriocin producers, but the most efficient isolate was MA7. Antibacterial activity of bacteriocin against some pathogenic bacteria was tested using well diffusion method. Bacteriocin was partially purified by ammonium sulfate precipitation, ion exchange using (DEAE)-Cellulose. After purification steps, three peaks were obtained. quantitative screening of bacteriocin involving the estimation of protein concentration and estimation of antibacterial activity showed that the large first peak was 1.6 mg/ml, 640 U/ml.